从内容与人物看《游仙窟》与唐 代文士生活面貌的切实性 = Analysis on how “You Xian Ku” reflects a literati’s life style during the Tang Dynasty - 曲畅 Chang, Qu (2017)
张鷟（658年－730年）是初唐时期较有影响的小说作家，其作品《游仙窟》是一篇体现了通俗小说“娱乐消遣”功能的骈文体小说。文本看似以游仙的主题，实而却反应了唐代文士的现实生活。虽是以虚幻的仙窟设定为背景，但其中不论对于主角本身文人气质的体现还是在衣着、宴席礼数和房间陈设的描绘却不乏符合唐代文人的生活面貌。本文将以《游仙窟》的故事叙述顺序为线路，着重分析文中与唐代文士生活风貌相符的内容。首先，从文中对十娘五嫂服饰妆容、宴客酒席的摆设礼仪、十娘闺房内的陈设三方面描述着手，参照历史记录、出土文物等多方面资料探讨文中所述如何反映唐代现实生活风貌。再来，从主人公张郎所展现的文人形象为突破口看唐代文士通过表现才学追求敬仰的心理以及放荡风流的特质。从而进一步从由虚幻铺开的真实一角度分析《游仙窟》以游仙为题，却切实反映唐代风貌的文学作品特质。Zhang Zhuo (658-730) is an influencing novel writer during the early Tang Dynasty. One of his most prominent work, “You Xian Ku”, is a popular novel which includes rhythmical prose that embodies the “entertainment” function. On the surface, the story seems to be revolving around mythical fairies. However, through the fictional story, “You Xian Ku” actually reflects the non-fictional life of a literati during the Tang Dynasty. This can be shown through the author’s illustration of the protagonist’s temperament, the fairies’ outfits, banquet courtesy as well as room furnishings. The focus of this report will be comparing the author’s illustration to the actual life of a literati during the Tang Dynasty. Firstly, this report will be starting with the author’s description regarding the makeup and outfit, banquet etiquette, as well as boudoir furnish of two fairies, Shi Niang and Wu Sao. With reference to historical records, unearthed cultural relics and other information as evidence, this report will be proving on the closeness of the text in comparison with the actual life during Tang Dynasty. Secondly, this report will analyze from the perspective of the protagonist, Zhang Lang, to understand how the literati utilize their talents in search for respect and fluttering romance. Through these factors, this report will prove that “You Xian Ku” is a prose novel which reflects a literati’s life style during the Tang Dynasty.